Metode Penyimpanan Bakteri Xanthomonas Oryzae pv. oryzae Penyebab Penyakit Hawar Daun Bakteri Pada Tanaman Padi Menggunakan Glycerol - Santi Sariasih; Fitri Widiantini; Wiwin Widiawati (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
The existence of Xanthomonas oryzae pv. oryzae, the bacteria which causes Bacterial Leaf Blight of rice, is really necessary for the laboratory to support the research activities of the phytopathology experts. Long-term preservation by using glycerol under -20°C can be conducted to preserve the culture’s availability to stay viable in the laboratory. This research aimed to determine the glycerol concentration that is able to preserve the viability and pathogenicity of Xanthomonas oryzae pv. oryzae bacteria after being preserved for 3 and 6 months. This experiments were performed using Completely Randomized Design which comprised of six treatments and four replications, they were: glycerol 50%, 40%, 30%, 20%, 10%, and control (without glycerol). The results of this study showed that viability of Xanthomonas oryzae pv. oryzae that was preserved within 20% glycerol solution for 6 months was different compared to control group. The number of Xanthomonas oryzae pv. oryzae bacteria on 20% glycerol was 4,49 x 109 CFU/ml, while on control group was 1,76 x 109 CFU/ml. 20% glycerol concentration had significant effect on the Bacterial Leaf Blight symptoms’ length after 6-months preservation that observed on the 7th day after incubation. The Bacterial Leaf Blight symptoms’ length on 20% glycerol treatment group was 46,2 mm and 22,7 mm on control group. Meanwhile for the 3 months preservation, the administration of glycerol did not show any significant effect on the Xanthomonas oryzae pv. oryzae’s viability and the Bacterial Leaf Blight symptoms’ length.